Nitrate reductase enzymes in alga Chattonella subsalsa are regulated by environmental cues at the translational and post-translational levels - Wang, Yanfei; Johnson, Gretchen I.; Postles, Anna; Coyne, Kathryn J. (Frontiers in Microbiology, 2023)
Nitrate reductase (NR) catalyzes the rate-limiting step in nitrate assimilation. Plant and algal NRs have a highly conserved domain architecture but differ in regulation. In plants, NR activity is regulated by reversible phosphorylation and subsequent binding of 14-3-3 proteins at a conserved serine residue. Algal NRs typically lack 14-3-3 binding motifs, which have only recently been identified in a few algal species. Previous research indicates that the alga, Chattonella subsalsa, possesses a novel NR, NR2-2/2HbN (NR2), which incorporates a 2/2 hemoglobin domain. A second NR (NR3) in C. subsalsa lacks the cytochrome b5 (heme-Fe) domain but includes a putative binding motif for 14-3-3 proteins. The expression of NR2 and NR3 genes indicates that NR2 transcript abundance was regulated by light, nitrogen source, and temperature, while NR3 transcript levels were only regulated by light. Here, we measured total NR activity in C. subsalsa and the potential for regulation of NR activity by putative 14-3-3 binding proteins. Results indicate that NR activity in C. subsalsa was regulated by light, nitrogen source, and temperature at the translational level. NR activity was also regulated by endogenous rhythm and temperature at the post-translational level, supporting the hypothesis that NR3 is regulated by 14-3-3 binding proteins. Together with a previous report describing the regulation of NR gene expression in C. subsalsa, results suggest that C. subsalsa responds to environmental conditions by differential regulation of NRs at transcriptional, translational, and post-translational levels. This flexibility may provide a competitive advantage for this species in the environment. To date, this is the first report which provides evidence for the potential post-translational regulation of NR by 14-3-3 proteins in algal species and suggests that regulatory mechanisms for NR activity may be shared between plants and some algal species.